Good Practices for Sustainable Food Consumption and Reduction of Food Waste in Bulgaria - Vasileva, Elka; Stefanov, Stilian; Tipova, Nina; Ivanova, Daniela (Research Papers, 2022)
The present study focuses on a little-studied area in the Bulgarian context - sustainable food consumption. The study aims to map good practices in this field in Bulgaria. The Food System Mapping method has been applied to gather information on good practices, while meeting the requirements for appropriate selection of participants and for visual and interactive presentation of shared information. The mapping was carried out during a discussion with 41 stakeholder representatives since the imposition of sustainable food consumption patterns in the country, divided into 7 groups. After content analysis the answers of the participants in the discussion have been coded, categorized and positioned at the appropriate stages. The results obtained were validated by five experts in this field. A discussion of the identified good practices in terms of their position at the relevant stage of the sustainable agri-food chain has been held: sustainable food production; sustainable food processing and distribution; sustainable food consumption and prevention of food loss and waste. The role of stakeholders in sustainable food consumption and in reducing food waste in Bulgaria along the sustainable agri-food chain has been also revealed.In conclusion, the need for change of the business models of production, processing, distribution, trade, and imposition and dissemination of the identified good practices for change of consumer behaviour and prevention of food loss and waste has been emphasized.
Keywords: Good practices; Agri-food chain; Sustainable food consumption; Reduction of food waste; Bulgaria